MANAGEMENT DEVELOPMENT OF TEACHER PROFESSIONALITY IN IMPROVING LEARNING EFFECTIVENESS - Saria Santi; Sultan Syahril; Yuli Habibatul Imamah (UNISAN JURNAL, 2024)
This research aims to find out how management develops professionalism and increases learning effectiveness. This research uses a qualitative design. Data collection techniques use interviews, observation and documentation. The Role of Teachers in Management of Teacher Professional Development In Increasing the Effectiveness of Learning at SMP N 1 Kotabumi as a facilitator, role Teacher mentor, war Teacher motivator, role Teacher organizer, the role of the teacher as a human resource, this is of course produce results Which positive that is exists Management Development Professionality Teacher In Increase Effectiveness of Learning at SMP N 1 Kotabumi Academic Year. Factors Which influence Management Development Professionality Teacher In Increase Effectiveness Learning at SMP N 1 Kotabumi is as follows: Internal Factors, factor Internal, namely factors that come from in the teacher himself which consists of physiological factors and factor psychology, namely lack Professional from within Teacher. External factors are factors that come from outside the participant educate. These factors include family, school and participant factors educate among them factor family And factor school.